Deskripsi Kecakapan Matematika Siswa pada Materi Trigonometri - Luhukay, Agnes Stefine; Rontos, Ferdy; Yuwono, Layli Rahmania; Ramadani, Leni; Muchlis, Ahmad (Department of Mathematics, Universitas Negeri Gorontalo, 2024)
One of the things that teachers must do is assessment. Assessment is useful for collecting information that is used as the basis for planning and action in improving and achieving learning goals. However, in real life practice it is not easy for teachers to do it. Therefore, this study aims to provide an overview for teachers in conducting mathematics assessments referring to the five strands of mathematical proficiency, especially in trigonometry unit lesson. The method used in this research is descriptive qualitative method. Some of the results obtained from this study, namely: (1) Conceptual understanding proficiency include understanding and using related trigonometry concepts and connecting related concepts, such as the concept of comparison, algebraic operations, and the concept of triangles; (2) procedural fluency relates to students' ability to choose procedures and how to use them. Some of the procedures carried out by students include the procedure of communicating information from the existing problem, performing operations, concluding the solution to the problem; (3) strategy competency encountered to solve trigonometric problems is to make illustrative images; (4) adaptive reasoning can be seen from their ability to understand the trigonometric problems given and the information contained therein. This is indicated by students' arguments in the form of image communication and algebraic expressions written down in solving the problem; (5) productive disposition will develop if the other four proficiencies develop.